2011
DOI: 10.1055/s-0031-1285833
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Mitochondrial Dysfunction is Evident in Type 2 Diabetes in Association with Modifications of Mitochondrial Anti-Oxidant Stress Proteins

Abstract: Objective: Mitochondrial dysfunction and oxidative stress in insulin responsive tissues is implicated in the pathogenesis of type 2 diabetes. Whether these perturbations extend to other tissues and contribute to their pathophysiology is less well established. The objective of this study was to investigate platelet mitochondria to evaluate whether type 2 diabetes associated mitochondrial dysfunction is evident in circulating cells. Method: A pilot study of mitochondrial respiratory function and proteomic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 15 publications
5
71
1
Order By: Relevance
“…The number of cells was adjusted to 2.5 × 10 6 cells per transfection cuvette to increase cell viability after transfection (44). To evaluate the effect of the sera from subjects on the glucose, 1 mM sodium pyruvate, 31 mM NaCl, 2 mM GlutaMax, pH 7.4) and plated on CellTak-coated (BD Biosciences) XF24-well plates, as previously described (46). Cells were maintained at 37°C in a non-CO 2 incubator for at least 1 hour before the assay.…”
Section: Study Participants and Protocolmentioning
confidence: 99%
“…The number of cells was adjusted to 2.5 × 10 6 cells per transfection cuvette to increase cell viability after transfection (44). To evaluate the effect of the sera from subjects on the glucose, 1 mM sodium pyruvate, 31 mM NaCl, 2 mM GlutaMax, pH 7.4) and plated on CellTak-coated (BD Biosciences) XF24-well plates, as previously described (46). Cells were maintained at 37°C in a non-CO 2 incubator for at least 1 hour before the assay.…”
Section: Study Participants and Protocolmentioning
confidence: 99%
“…1,2 Identification of specific mitochondrial alterations in platelets from patients with a variety of pathologies including Parkinson disease, 1,3,4 sepsis, 2,5 and type 2 diabetes melllitus 6,7 have established that platelets can be used as biomarkers for systemic mitochondrial dysfunction. However, the exact role of bioenergetics in regulating platelet thrombotic function is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…This is clinically important since mitochondrial dysfunction can initiate a series of cellular events that promote pro-inflammatory signaling pathways or lead to cell death. Several studies have characterized mitochondrial function of peripheral blood mononuclear cells and platelets in conditions such as fibromyalgia, diabetes, septic shock, and Alzheimer's disease [3][4][5][6][7] . For example, a recent study evaluated the bioenergetics of platelets as a marker for mitochondrial function and found that platelets from Type 2 diabetic patients had diminished mitochondrial oxygen consumption 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have characterized mitochondrial function of peripheral blood mononuclear cells and platelets in conditions such as fibromyalgia, diabetes, septic shock, and Alzheimer's disease [3][4][5][6][7] . For example, a recent study evaluated the bioenergetics of platelets as a marker for mitochondrial function and found that platelets from Type 2 diabetic patients had diminished mitochondrial oxygen consumption 7,8 . From these findings and others, it is clear that monocytes, lymphocytes, neutrophils, and platelets can serve as surrogate markers of changes in bioenergetics under pathological conditions since they survey the systemic circulation and may reflect local and global metabolic changes.…”
Section: Introductionmentioning
confidence: 99%